Employee performance based on work motivation, work environment, and work discipline - Emela, Satia; Gemina, Dwi; Kartini, Tini (Jurnal Ekonomi, 2024)
Human resources are the main factor for the success of an organization or company, which must be managed as well as possible. The goal on this investigate was to investigate the impact of work motivation, work environment, and work discipline on employee performance at PT. Cida Supra Metalindo. The sample in this study was 43 employees using non-probability sampling with saturated sampling technique. The analytical method used is descriptive and verification methods. Data collection techniques through questionnaires, observation, interviews and literature study. The data was analyzed using multiple linear regression. According to the findings of this study, work motivation, work environment, and work discipline all have a favorable and considerable impact on staff  performance, either simultaneously or partially. Work discipline is the most important factor influencing worker performance at PT. Cidas Supra Metalindo. Therefore, you must always supervise employees so that they always comply with the rules that have been set.